The major age as a requirement for the registral rectification of sex and the name: a question of fundamental rights - Juan Manuel Sánchez Freyre (Revista Sobre la Infancia y la Adolescencia)
Constitutional transcendence of the requirement of majority for the recognition of the right to sexual identity and the change in the registration of sex in the Civil Registry in the case of transsexual people and their incardination in the limitations to the capacity to act Minors. Diversity of legal treatment of the age and its legislative and jurisprudential treatment in attention to the progressive acquisition of discernment and ability to understand and to issue its will in the best interest of the minor. The principle of the best interest of the child as a frame of reference to analyze each specific case in defense of fundamental rights in general and its concretion in the case of minors. The difficulty of assessing this indeterminate legal concept.